2011
DOI: 10.1152/ajpregu.00265.2011
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic activity of neurons in the rostral ventrolateral medulla of conscious cats: effect of removal of vestibular inputs

Abstract: -Although it is well established that bulbospinal neurons located in the rostral ventrolateral medulla (RVLM) play a pivotal role in regulating sympathetic nerve activity and blood pressure, virtually all neurophysiological studies of this region have been conducted in anesthetized or decerebrate animals. In the present study, we used time-and frequency-domain analyses to characterize the naturally occurring discharges of RVLM neurons in conscious cats. Specifically, we compared their activity to fluctuations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…The RVLM also provides a major pathway through which vestibular signals are conveyed to sympathetic preganglionic neurons in the spinal cord, as indicated by the observation that bilateral chemical lesions of the RVLM abolished VSR (328). In conscious cats, a significantly higher fraction of RVLM neurons exhibited cardiac-related activity, or rhythmic bursts of action potentials synchronized with the cardiac cycle, after removal of vestibular inputs (27). In addition, a bilateral labyrinthectomy resulted in a significant reduction in the spontaneous activity of RVLM neurons, including those with cardiac related activity (27).…”
Section: Recovery Of Posturally-related Cardiovascular Responses Follmentioning
confidence: 99%
“…The RVLM also provides a major pathway through which vestibular signals are conveyed to sympathetic preganglionic neurons in the spinal cord, as indicated by the observation that bilateral chemical lesions of the RVLM abolished VSR (328). In conscious cats, a significantly higher fraction of RVLM neurons exhibited cardiac-related activity, or rhythmic bursts of action potentials synchronized with the cardiac cycle, after removal of vestibular inputs (27). In addition, a bilateral labyrinthectomy resulted in a significant reduction in the spontaneous activity of RVLM neurons, including those with cardiac related activity (27).…”
Section: Recovery Of Posturally-related Cardiovascular Responses Follmentioning
confidence: 99%
“…A direct vestibular projection to the RVLM region has also been reported [18]. A series of studies by Yates and co-workers [19-21] demonstrated that signals coming from peripheral vestibular organs via the vestibular nucleus affect blood pressure, perhaps through the classic pathway of cardiovascular regulation. Electrophysiological and morphological studies have also shown that the RVLM is a key area in the pathway conveying vestibular signals to the gray substance in the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that higher brain areas adjust the responsiveness of neurons in the vestibulosympathetic reflex pathway to vestibular inputs, so that the gain of the vestibulosympathetic reflex is appropriate for the ensuing movement or postural change (32). Recordings from conscious animals also provided evidence that following a bilateral labyrinthectomy, the gain of the baroreceptor reflex is adjusted by descending signals from supratentorial brain regions (251). As noted above, a number of supratentorial regions provide inputs to neurons that comprise the vestibulosympathetic reflex pathway, and it is unclear which of these regions participates in adjusting the response gain, and where along the pathway (vestibular nuclei, NTS, CVLM, RVLM) the gain adjustments occur.…”
Section: Transformation Of Vestibular Reflexes By Descending Pathwaysmentioning
confidence: 99%
“…Neurophysiologic experiments on neurons that constitute vestibulosympathetic pathways are in their infancy, and just two studies (184, 251) have monitored in conscious animals the activity of RVLM neurons that play a key role in regulating sympathetic nervous system activity. Little attention has been paid to the contributions of other pathways to vestibulosympathetic responses, including those originating in the medial reticular formation, raphe nuclei, and locus coeruleus that provide monosynaptic or polysynaptic inputs to both limb motoneurons and sympathetic preganglionic neurons (5356).…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%